Timeliness Of Annual Financial Statement Submission: Preliminary Empirical Evidence From Indonesia - Na’im, Ainun (Asian Academy of Management (AAM), 2000)
The study investigates the effects of size, profitability, and financial distress on information regulatory noncompliance (IRN) of firms listed in the Jakarta Stock Exchange (JSX). The firms’ IRN in this study is measured by the firm noncompliance on the timeliness regulation, i.e. whether firms submit financial statement to the Indonesian Capital Market Supervisory Agency (BAPEPAM) on, before, or after the due date. The purpose of this study is to provide preliminary empirical evidences about the timeliness of financial reporting which is still very limited in emerging market such as Indonesia. This study found that return on asset (ROA) is a determining factor to noncompliance behaviour of the firms in meeting the timeliness requirement. Inconsistent with previous studies (e.g., Whittred 1980 and Givoly and Palmon 1982), this study found that auditor opinion has no association with the noncompliance since most of the financial statements of noncomplying firms have unqualified opinions. The results are partially consistent with previous studies such as those of Schwartz and Soo (1996).